Aerosol therapy during non-invasive mechanical ventilation: Review of key technical factors and clinical implications - (:unkn) unknown (My University, 2013)
Whereas the evidence supporting aerosol delivery during invasive mechanical ventilation (IMV) is well described, this is not the case for non-invasive mechanical ventilation (NIV) in the treatment of chronic obstructive pulmonary disease or asthma. Several issues that seem to significantly influence aerosol delivery during NIV are still not resolved, such as patient characteristics, the characteristics of the ventilator, ventilatory mode (continuous positive airway pressure vs. bi-level NIV), the use of metered-dose inhalers vs. nebulization, and the interface (nasal vs. facial mask). The aim of this paper is to review the current knowledge of technical factors related to the delivery of aerosol therapy during NIV. In this technical review and analysis, we found that, owing to the still-limited data obtained in clinical practice, aerosol therapy supported by NIV may be considered an added value for improving bronchial obstruction. Despite a strong rationale for the use of NIV to deliver bronchodilators in severe acute obstructive airways diseases, the clinical evidence supporting the largescale application of this practice remains limited. Further investigation is required to achieve a strong level of evidence to support the routine implementation of this therapy.
Keywords: Aerosol therapy; Bi-level positive airway pressure; Chronic obstructive pulmonary disease; Continuous positive airway pressure; Metered-dose inhaler; Nebulizers; Non-invasive mechanical ventilation